2014
DOI: 10.1007/s10899-013-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling and Homelessness: Results from an Epidemiologic Study

Abstract: The purpose of this study was to investigate the prevalence of gambling disorder and comorbid psychiatric disorders in a homeless population and identify features related to potential subtypes. At baseline, participants were administered a structured interview including socio-demographic sections of the National Comorbidity Study (NCS) interview; seven diagnostic sections of the Diagnostic Interview Schedule (DIS); the alcohol and drug abuse sections of the Composite International Diagnostic Interview-Substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 25 publications
6
56
1
Order By: Relevance
“…Findings are similar to those observed among people addicted to cocaine who are in treatment (Hall et al 2000;Toneatto and Brennan 2002) and those reported by consumers of alcohol or other drugs in treatment (Barnes et al 2015). Also, results align with previous studies of active consumers of substances such as the homeless (Nower et al 2014;Shaffer et al 2002;Sharman et al 2015). The present study findings highlight the vulnerability of community-based cocaine users attending homeless and harm reduction programs to gambling problems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Findings are similar to those observed among people addicted to cocaine who are in treatment (Hall et al 2000;Toneatto and Brennan 2002) and those reported by consumers of alcohol or other drugs in treatment (Barnes et al 2015). Also, results align with previous studies of active consumers of substances such as the homeless (Nower et al 2014;Shaffer et al 2002;Sharman et al 2015). The present study findings highlight the vulnerability of community-based cocaine users attending homeless and harm reduction programs to gambling problems.…”
Section: Discussionsupporting
confidence: 91%
“…Considering nearly one in five cocaine users in this sample suffered from the harmful consequences of gambling activities, it is crucial that the resources they are offered address problems associated with these types of activities (Nower et al 2014). Research by Holdsworth and Tiyce (2013) has previously emphasized the secretive nature of problems gambling, stemming perhaps from feelings of shame and from associated stigma, which underscores the importance of engaging in proactive efforts to detect them.…”
Section: Discussionmentioning
confidence: 99%
“…As a postal survey, the BGPS did not include various demographic sectors including the homeless, and a number of international studies have reported elevated levels of problem gambling in the homeless, in the range of 11.6–25% (LePage, Ladouceur, & Jacques, 2000; Matheson, Devotta, Wendaferew, & Pedersen, 2014; Nower, Eyrich-Garg, Pollio, & North, 2015; Shaffer, Freed, & Healea, 2002; Sharman, Dreyer, Aitken, Clark, & Bowden-Jones, 2015). In the first study to examine this in the UK, we recruited 456 homeless individuals from day centers and hostels in Westminster, London.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nower et al. (2015) found that 63% of their sample met lifetime criteria for alcohol abuse or dependence, and 60.4% met lifetime criteria for substance abuse or dependence. In a study of people sleeping rough in London, 36% were drug dependent and 25% were alcohol dependent (Fountain, Howes, Marsden, Taylor, & Strang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…56 For instance, a person that gambles may be less likely to own his or her own home and thus lack the necessary electronic infrastructure at their place of residence. In such circumstances, Internet cafes can help to bridge the digital divide, providing access to the Internet.…”
Section: Digital Franchise and Gambling Involvementmentioning
confidence: 99%